Reference service for publications of intergovernmental organizations : papers from an IFLA workshop, Paris, August 24, 1989 - Kagan, Alfred; International Federation of Library Associations and Institutions (München ; New York : K.G. Saur, 1991)
These conference papers were written for a practical all-day workshop on "Reference Service for Publications of Intergovernmental Organizations". The first two papers dealt with recent survey results from a survey of bibliographic services of International Intergovernmental Organizations, and from a user study of information from International Governmental Organizations. It further described how librarians from seven Intergovernmental Organizations answer four most important types of reference questions that arise form their daily work.
Includes bibliographical references.
ne 29/01/2020
Loans
Keywords: International agency libraries; International agency publications; International agency libraries--Reference services; International agency publications--Bibliography--Methodology